(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Bloodstream infections in neonates are one of the most life-threatening infections in them . In this study, a total of 140 blood samples werecollected from neonates at AL-Batoul Teaching Hospital for Gynecology and Pediatrics in Baqubah/Diyala, their ages ranging from 1 dayto 28 days during the period from November 2021 to March 2022. The samples were subjected to a culture study as well as hematologicaland immunological tests (CRP, measuring the level of IL-27 and IL-33). Out of total cultured samples 45 give a positive blood culture, 45specimens from blood culture negative was chosen to become (control group) to be comparable to positive culture specimens. The resultsof the CRP test showed in the Gram-negative bacteria group, the positive result was 76.92% (10 of 13). In the Gram-positive bacteria group,the positive CRP percentage was 84.85% (28 of 33). While in the control group the positive result was 13.33% (6 of 45) , significantdifferences appeared between the compared groups. The results showed the mean levels of IL-27 in the sepsis patient group and controlgroup were (21.14 ± 1.01 and 14.49 ± 0.34 pg/ml, respectively). also showed the mean levels of IL-33 were in the sepsis patient group andcontrol group (250.28 ± 15.75 and 101.16 ± 3.38 pg/ml, respectively). There was a significant increased level of IL-27 and IL-33 in the sepsispatients’ group compared to the control group.